Severe Adverse Drug Reaction to Gadobenate Dimeglumine. (2009) - Singer, Benjamin D.; Woodrick, Robert S.; Pedicano, Jennifer B.
Abstract : A 57-year-old man was admitted to our hospital for evaluation and management of stroke in the setting of an atrial septal defect. Shortly after receiving gadobenate dimeglumine for magnetic resonance imaging of the pelvic vessels, he experienced cardiac arrest from which he was resuscitated. His course was complicated by profound distributive shock. The presumed cause was a severe anaphylactic or anaphylactoid reaction to the gadolinium-based compound that he received.